Does the impact of a plant-based diet during pregnancy on birth weight differ by ethnicity? A dietary pattern analysis from a prospective Canadian birth cohort alliance. Issue 11 (14th November 2017) - Zulyniak, Michael A; de Souza, Russell J; Shaikh, Mateen; Desai, Dipika; Lefebvre, Diana L; Gupta, Milan; Wilson, Julie; Wahi, Gita; Subbarao, Padmaja; Becker, Allan B; Mandhane, Piush; Turvey, Stuart E; et al.
Abstract : Objective: Birth weight is an indicator of newborn health and a strong predictor of health outcomes in later life. Significant variation in diet during pregnancy between ethnic groups in high-income countries provides an ideal opportunity to investigate the influence of maternal diet on birth weight. Setting: Four multiethnic birth cohorts based in Canada (the NutriGen Alliance). Participants: 3997 full-term mother–infant pairs of diverse ethnic groups who had principal component analysis-derived diet pattern scores—plant-based, Western and health-conscious—and birth weight data. Results: No associations were identified between the Western and health-conscious diet patterns and birth weight; however, the plant-based dietary pattern was inversely associated with birth weight (β=−67.6 g per 1-unit increase; P<0.001), and an interaction with non-white ethnicity and birth weight was observed. Ethnically stratified analyses demonstrated that among white Europeans, maternal consumption of a plant-based diet associated with lower birth weight (β=−65.9 g per 1-unit increase; P<0.001), increased risk of small-for-gestational age (SGA; OR=1.46; 95% CI 1.08 to 1.54;P=0.005) and reduced risk of large-for-gestational age (LGA; OR=0.71; 95% CI 0.53 to 0.95;P=0.02). Among South Asians, maternal consumption of a plant-based diet associated with a higher birth weight (β=+40.5 g per 1-unit increase; P=0.01), partially explained by cooked vegetable consumption. Conclusions: Maternal consumption of a plant-based diet during pregnancy is associated with birth weight. Among white Europeans, a plant-based diet is associated with lower birth weight, reduced odds of an infant born LGA and increased odds of SGA, whereas among South Asians living in Canada, a plant-based diet is associated with increased birth weight.